2021
DOI: 10.36456/penamas.vol4.no2.a2784
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Quiz Bot Telegram Dalam Pembelajaran Menyimak Bahasa Inggris

Abstract: Peguasaan dan pemanfaatan teknologi untuk menunjang keberhasilan pembelajaran sudah menjadi keharusan dan tuntutan di era Revolusi Industri 4.0, terlebih di masa pandemi COVID-19. Guru sebagai garda terdepan untuk kemajuan pendidikan dengan demikian harus membekali diri dengan teknologi pembelajaran berupa Sistem Manajemen Pembelajaran atau Learning Management System (LMS) seperti Google Classroom, Edmodo, Canvas, Telegram dan lain sebagainya. Oleh karena itu, artikel ini bertujuan untuk menjelaskan tentang pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The existence of images, audio and video besides being able to convey material more clearly, especially in the digestive system which has complex material and abstract parts will make students not bored while doing independent learning. In line with the opinion of Hidayat et al (2021) that with the text, image, questions and audio features on the telegram quiz bot, it can be utilized in material listening skills. This means that students will be more focused and focused in understanding the processes and explanations of the digestive system material.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The existence of images, audio and video besides being able to convey material more clearly, especially in the digestive system which has complex material and abstract parts will make students not bored while doing independent learning. In line with the opinion of Hidayat et al (2021) that with the text, image, questions and audio features on the telegram quiz bot, it can be utilized in material listening skills. This means that students will be more focused and focused in understanding the processes and explanations of the digestive system material.…”
Section: Resultsmentioning
confidence: 97%
“…This research shows that student responses strongly agree if telegram media is used as a learning support with a score of 86.47%. Study Hidayat et al (2021) also shows that one of the features in telegram, namely the telegram quiz bot, can be used as a medium to improve listening skills.…”
Section: A Introductionmentioning
confidence: 97%
“…There are several steps in using the Telegram Quiz Bot: open the Telegram application on the device, type @quizbot in the Telegram Search, select and click the Quiz Bot, then press 'START' and then follow the directions (Hidayat, et al, 2021). The According to Table 3, the average score obtain 3,1 which is included in the "Good" category based on the assessment criteria in Based on the Table 6 above, the homogenity test result obtain the significant valus is 0,084 which means it is greater than 0.05 then it can be concluded that the sample was come from the homogeneous population.…”
Section: Methodsmentioning
confidence: 99%
“…The Systemic literature reviewed by Citrawati (2021) found that the Telegram Quiz Bot positively contributed to creating an enjoyable and stress-free learning environment for promoting students' motivation. According to Hidayat et al (2021), using the help of Quiz Bot Telegram on the Problem Based Instruction learning model is considered to help teachers in correcting assigned task and was able to save time because it already saved one answer correctly about the quiz that will be tested, as well as on the Quiz Bot application there are statistical results of the order of assessment seen from the time of processing the questions and the results of the value of the answers given by the lecturer.…”
Section: Learning Motivationmentioning
confidence: 99%